Galacto-oligosaccharides fed during gestation increase Rotavirus A specific antibodies in sow colostrum, modulate the microbiome, and reduce infectivity in neonatal piglets in a commercial farm setting - Lee, Adam; Liang, Lu; Connerton, Phillippa L.; Connerton, Ian F.; Mellits, Kenneth H. (Frontiers in Veterinary Science, 2023)
Rotavirus A is a major cause of acute dehydrating diarrhea in neonatal pigs resulting in significant mortality, morbidity, reduced performance and economic loss. Commercially available prebiotic galacto-oligosaccharides are similar to those of mammalian milk and stimulate the development of the microbiota and immune system in neonates. Little is known about the effects of supplementing sows’ diets with galacto-oligosaccharides during gestation. This study aimed to determine if dietary galacto-oligosaccharide supplementation during gestation could improve immunity, reduce rotavirus infection and modulate the microbiota in sows and neonatesl in a commercial farm setting with confirmed natural endemic rotavirus challenge. In a randomised controlled trial, control sows received lactation diet with no galacto-oligosaccharide supplementation and test sows received lactation diet with 30g/day galacto-oligosaccharide top-dressed into feed daily, seven days before farrowing. Colostrum was collected from sows 24 hours post-partum and tested for rotavirus specific antibodies. Fecal samples were collected from sows and piglets three days post-partum, tested for rotavirus A by qPCR and the microbiome composition assessed by 16s rRNA gene sequencing. Supplementation with galacto-oligosaccharides during gestation significantly increased rotavirus-specific IgG and IgA in sow colostrum and reduced the number of rotavirus positive piglet fecal samples. Abundance of potential pathogens Treponema and Clostridiales were higher in fecal samples from non-galacto-oligosaccharide fed sows, their piglets and rotavirus positive samples.This study demonstrates that galacto-oligosaccharide supplementation during gestation significantly increases rotavirus specific IgG and IgA in sow colostrum thereby reducing neonatal rotavirus infection and suppresses potential pathogenic bacteria in nursing sows and neonatal piglets.